Immigration Crisis in Palestine (1933–1936) as Reflected in Periodical Press of United States - M. I. Tuluzakova; S. O. Buranok (Научный диалог, 2024)
The image of Palestine during the years 1933 to 1936 was shaped in the periodical press of the United States under the influence of the “colonial discourse”. In the first half of the 1930s, the issue of Jewish immigrants became one of the central themes in the “Palestinian question”. The materials from the periodical press allow for an exploration of how perceptions regarding the causes of the crisis in the Middle East evolved within the informational discourse of the United States; how the representations of Arabs, Jews, and Great Britain underwent transformation. Publications from American newspapers provide insights into evaluations of British measures aimed at resolving the immigration crisis in Palestine during the 1930s. An analysis of U.S. newspapers reveals distinctive features in the construction of the images of the Jewish and Arab populations of Palestine. It identifies who was categorized as “the other”. The first half of the 1930s proved decisive for American public opinion in prioritizing positions within the context of the Middle Eastern conflict. The material presented in this article vividly illustrates the stages of evolving assessments of the situation in Palestine from 1933 to 1936. The study examines the manipulative techniques and strategies employed by American periodicals in the 1930s concerning Palestine, thereby providing a clearer understanding of how the issue of Jewish immigration was integrated into the broader narrative of Palestine within U.S. periodical literature.